1985
DOI: 10.1210/endo-116-1-138
|View full text |Cite
|
Sign up to set email alerts
|

α-Melanocyte-Stimulating Hormone Stimulation of Aldosterone Secretion in Hypophysectomized Rats*

Abstract: Intact and hypophysectomized male rats on low and high sodium diets were treated with sc infused ACTH and alpha MSH, and the levels of aldosterone and corticosterone were determined in truncal blood. Plasma aldosterone levels were lower in hypophysectomized animals on the low sodium diet than in intact animals on the low sodium diet. Alpha MSH (8 micrograms/day) restored plasma levels of aldosterone to normal in hypophysectomized rats on the low sodium diet. ACTH (6 micrograms/day) did not cause significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This stimulation has been related to the role of ·MSH in the regulation of aldosterone synthesis in the glomerular zone of the adrenal cortex. Distinct experimental data indeed strongly support the stimulatory effect of ·MSH on aldosterone production [Vinson et al, 1980;Shenker et al, 1985]. More recently, however, Allen et al [1995] found no modification of the aldosterone synthase mRNA in transgenic mice in which POMC-expressing pituitary cells (i.e.…”
Section: Functional Implicationsmentioning
confidence: 84%
“…This stimulation has been related to the role of ·MSH in the regulation of aldosterone synthesis in the glomerular zone of the adrenal cortex. Distinct experimental data indeed strongly support the stimulatory effect of ·MSH on aldosterone production [Vinson et al, 1980;Shenker et al, 1985]. More recently, however, Allen et al [1995] found no modification of the aldosterone synthase mRNA in transgenic mice in which POMC-expressing pituitary cells (i.e.…”
Section: Functional Implicationsmentioning
confidence: 84%
“…A possible interference between -MSH and the metoclopramide-induced long-term inhibition of the dopa¬ minergic control system of aldosterone secretion (Aguilera et al 1984) cannot be excluded. More¬ over, more recent in vivo evidence has shown that chronic -MSH administration is able to elicit aldosterone output only in hypophysectomized animals (Shenker et al 1985), so that these inves¬ tigators hypothesized the existence of a hypo¬ physeal inhibitory factor blocking -MSH effect. We cannot at present satisfactorily explain these discrepancies, but we want to stress that the doses of -MSH employed by Shenker et al (1985) were about 5-fold less than ours (8 µg vs 40 µg/day).…”
Section: Discussionmentioning
confidence: 99%
“…More¬ over, more recent in vivo evidence has shown that chronic -MSH administration is able to elicit aldosterone output only in hypophysectomized animals (Shenker et al 1985), so that these inves¬ tigators hypothesized the existence of a hypo¬ physeal inhibitory factor blocking -MSH effect. We cannot at present satisfactorily explain these discrepancies, but we want to stress that the doses of -MSH employed by Shenker et al (1985) were about 5-fold less than ours (8 µg vs 40 µg/day). It does not seem unreasonable to propose that such low and paraphysiological doses of -MSH may express their aldosterone stimulating effect only in animals lacking the physiological source of endogenous -MSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If glomerulosa output of corticosterone in the whole animal studies of Shenker et ai. 54 Aside from variations in the general methodology used, several different preparations of intact tissue have been used, including whole, uncut glands,60 quartered or halved glands,61 minced whole glands,62 and capsular preparations obtained by enucleatin the gland through a slit in the connective tissue.6' The term 'adrenal slices' was often used synonymously with quartered glands. 64 At first static incubations were used, with two different approaches to identifying putative glomerulotropic stimulants.…”
Section: In Vzvo: Circulating Plasmamentioning
confidence: 99%